Matthews, Bill. Interview about growing up in New Perlican and the goats in the community. - Barrett, Terra (2017)
Terra Barrett of the Heritage Foundation of Newfoundland and Labrador interviews Bill Matthews about growing up in New Perlican, goat memories, children's rhymes, and family stories as part of The Goats of New Perlican Oral History Roadshow Project in partnership with Heritage New Perlican.